The Effect of Islamic Financial Literacy, Trust, and Financial Self-Efficacy on Islamic Financial Inclusion - Natasya, Syifa; Achmad Muttaqin, Aminnullah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Although the Islamic financial sector continues to grow in Indonesia, the level of islamic financial inclusion remains relatively low. According to the SNLK 2024 report, the index of islamic financial inclusion stands at only 12,88%, indicating a gap between service availability and public utilization. This study aims to analyze the influence of Islamic Financial Literacy, trust, and financial self-efficacy on islamic financial inclusion in Indonesia. Using a quantitative approach and the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS), the study involved 217 respondents who are users of islamic financial services. The results show that all three independent variables have a positive and significant influence on islamic financial inclusion. Financial self-efficacy is the most dominant factor influencing public participation in islamic financial service, followed by trust and financial literacy. These findings contribute to the development of strategies to improve financial inclusion based on individual empowerment and public trust in islamic institutions. The study recommends that islamic financial institutions and the government strengthen practical financial literacy programs and expand access to service grounded in sharia principles.